Stabilization of Canine Pelvic Osteotomies with AO/ASIF Plates and Screws - Hunt, C.A.; Litsky, A S. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
Stabilization of pelvic osteotomy with a 2.7 mm dynamic compression plate (DCP) for the treatment of hip dysplasia, was performed in 42 operations in 27 dogs. Screw loosening was observed in 11 osteotomies (26%), plate bending in six cases (14%) and plate breakage in two cases (4%). An in vitro experiment using the pelvic bones of young mixed breed dogs showed no significant difference in the holding power of AO/ASIF 2.7 mm cortical, 3.5 mm cortical and 3.5 mm fully threaded cancellous screws in the body of the ilium. The 2.7 mm DCP has an advantage over the 3.5 DCP in stabilizing pelvic osteotomy because it allows more screws to be used per unit length of plate, which possibly results in a more stable fixation.
Keywords: Dynamic compression plate (DCP); Pelvic osteotomy; Hip dysplasia; AO/ASIF plates and screws